Ethically digital: contested cultural heritage in digital context - Rouhani, B (Indiana University Press, 2023)
Over the past century, our understanding of cultural heritage has evolved, and now, heritage is seen more as a process than a product. Although the advancement of digital technologies has significantly aided in the research, protection, management, interpretation, and education of cultural heritage, it also raises the question of how far this technology works in accordance with our current understanding of heritage as a process and is not taking a reductionist approach, in which heritage is cut off from its community and context. Ethical risks are higher for contested heritage, when meaning and values are questioned, or when people's ability to access and enjoy heritage is threatened. This paper discusses potential ethical risks regarding access, control, dissemination, and the digital economy by looking at existing approaches, guidelines, and principles in this field and a few digital heritage projects about contested heritage, and it questions whether the lack of an inclusive ethical framework could lead to a new kind of digital colonisation.